Whole-Exome Sequencing for Identification of Genetic Variants Involved in Vitamin D Metabolic Pathways in Families With Vitamin D Deficiency in Saudi Arabia - Alharazy, Shatha; Naseer, Muhammad Imran; Alissa, Eman; Robertson, Margaret Denise; Lanham-New, Susan; Chaudhary, Adeel G. (Frontiers in Genetics, 2021)
Background: Numerous research have found an association between vitamin D (vitD) status and single nucleotide polymorphisms (SNPs) in genes involved in vitD metabolism. It is notable that the influence of these SNPs on 25-hydroxyvitamin D (25(OH)D) levels might vary in different populations. We aimed in this study to explore for genetic variants in genes related to vitD metabolism in families with vitD deficiency in Saudi Arabia using whole exome sequencing (WES). Methods: This family-based WES study was conducted for 21 families with vitD deficiency (n=39) from Saudi Arabia. WES was performed for DNA samples, then obtained WES data was filtered and a number of variants were prioritized and validated by Sanger DNA sequencing. Results: Several missense variants in vitD related genes were detected in families. We determined two variants in Low-density lipoprotein 2 gene (LRP2) with one variant (rs2075252) observed in six individuals, while the other LRP2 variant (rs4667591) was detected in 13 subjects. Single variant in 7-dehydrocholesterol reductase (DHCR7) (rs143587828) and melanocortin 1 receptor (MC1R) (rs1805005) gene were observed in 2 subjects of 2 different families. Other variants in group-specific component (GC), cubilin (CUBN) and calcium-sensing receptor (CASR) gene were seen in index cases and controls. Polymorphisms in GC (rs9016) and CASR (rs1801726) were seen in majority of family cases (94% and 88%) respectively. Conclusion: In vitD deficient families in Saudi Arabia, we were able to detect a number of missense exonic variants including variants in GC (rs9016), CUBN (rs1801222), CASR (rs1801726) and LRP2 (rs4667591). However, the existence of these variants was not different between affected family members and non-affected controls. Additionally, we were able to find a mutation in DHCR7 (rs143587828) and a polymorphism in LRP2 (rs2075252) which may affect vitD levels and influence vitD status. However, further studies are required to confirm the association of these variants with vitD deficiency.